A study on the energy performance of a ground source heat pump utilized in the refurbishment of an historical building: comparison of different design options. (October 2017) - Pacchiega, Claudia; Fausti, Patrizio
Abstract: The European construction sector is facing a major challenge due to the actual impact on long-term energy consumption, caused by the large number of existing buildings. In order to achieve the 2012 energy efficiency directive (2012-27-EU) each European country must draw-up long-term national building renovation strategies. Furthermore, existing buildings, subject to major renovation, also have to meet the European minimum energy performance requirements, in term of energy needs and system efficiency, requested by the 2010/31/EU and 2009/28/CE directives. The aim of the European Commission is to reduce by 27% the actual energy building consumption and to increase the total amount of renewable energy used by 27% by 2030. In Italy, national and regional laws have already implemented these strategies in order to achieve the national energy goals. The design phase in refurbishment projects is often problematic. The decisions taken in the early stages of the design determine the final result; however, the assessment of the environmental performance only happens at the end of the design process. Moreover, historical buildings present many artistic and architectural constraints that make the process more difficult, especially in the application of envelope refurbishment measures. Therefore, even more than in modern buildings, it is necessary to focus efforts on plant efficiency and exploitation of renewable sources. Currently the application of alternative energy supply systems in common retrofit has not generally been fully explored, in particular for historical buildings. In this context, geothermal energy is becoming all around Europe one of the most interesting sources of renewable energy for heating and cooling by ground-coupled heat pumps. The aim of this work is to compare different system solutions in terms of economic impact and energy needs during a building's operating phase and to evaluate the sustainability of ground-coupled heat pump technology for heating and cooling. The test case is an historical single-family dwelling located in Northern Italy and built in 1800 with relevant architectural and artistic features. A range of generation system retrofit options are analyzed in order to evaluate the building's primary energy needs, renewable energy exploitation and actualized return costs in each case. The heating and cooling generation systems compared are heat pumps with different renewable sources (geothermal and external-air) and different control systems (on/off and variable-capacity). Results can be applied in comparable case studies to support refurbishment strategies design.